The population structure of Hemileia vastatrix in Brazil inferred from AFLP - Maia, T. A.; Caixeta, E. T.; Mizubuti, E. S. G.; Zambolim, L.; Maciel-Zambolim, E. (Australasian Plant Pathology, 2013)
Efforts to obtain durable resistant cultivars to coffee leaf rust have a long history of disappointment because of the lack of information on the Hemileia vastatrix evolutionary potential. In this study, the AFLP marker was used to analyze the genetic structure of a field population of H. vastatrix from different coffee genotypes cultivated in a wide geographic region of Brazil’s main production areas. A total of 91 isolates were sampled from genotypes of Coffea arabica, C. canephora and Híbrido de Timor/Icatu derivatives. Each isolate exhibited unique multilocus AFLP genotypes with no identical isolates obtained from the same geographical and host origins. This finding was corroborated by a small correlation between genetic similarity and geographic distance (R xy  = 0.31, P = 0.23). The analyses showed a low genetic differentiation (G ST  = 0.026) between the populations defined by a host and AMOVA analysis, most of the genetic variance (99.56 %) was attributed to differences within populations. In addition, based on the index of association (IA), the random mating possibility was not rejected (IA = 0.225, P = 0.123) for the population of H. vastatrix derived from C. canephora. This result suggested that H. vastatrix in Brazil behaves as a large undifferentiated population with a high level of genotypic diversity that is unstructured with regard to its geographic and host origins.
Keywords: Coffee leaf rust; Durable resistance; Population genetics; Coffea arabica; Coffea canephora